Regulatory policy and sanitation consortia in Minas Gerais (Revista de Estudos em Municipalidade, 2026)
This article analyzes the benefits provided by the new configurations of intermunicipal consortia for basic sanitation as instruments of regulatory public policy, considering their economic, social, and operational advantages. The qualitative and descriptive research is based on content analysis according to Bardin (1977), using the free software IraMuTeQ, with a dataset of 310 resolutions from intermunicipal regulatory agencies for basic sanitation in the state of Minas Gerais, Brazil. The results show that, in Minas Gerais, the creation of regulatory consortia has contributed to the improvement of sanitation services in participating municipalities, as they represent an effective regulatory public policy strategy by strengthening governance through regulatory tariff instruments, increasing the efficiency of basic sanitation service delivery, and promoting greater equity in access to these services. The findings confirm theoretical propositions that emphasize the strategic role of public regulation.
Keywords: Regulatory Public Policy; Regulatory Agency; Intermunicipal Consortium; Basic Sanitation; Municipal Public Management